P71 Does mismatch repair (MMR) deficiency have prognostic significance in low-risk endometrioid endometrial cancers?. (1st November 2019) - Kim, SR; Pina, A; Albert, A; McAlpine, J; Wolber, R; Gilks, B; Carey, M; Kwon, J
Abstract : Introduction/Background: Mismatch repair deficiency (MMRd) is observed in 25–30% of all endometrial cancers. This can be detected by the absence of MMR protein staining on immunohistochemistry (IHC). Only 10% of women with MMRd have Lynch syndrome, but MMRd may still have prognostic significance. The objective of this study was to compare clinical outcomes between MMR deficient and proficient low-risk endometrioid endometrial cancers (stage IA, grade 1/2). Methodology: This was a retrospective population-based cohort study of all low-risk endometrial cancers from Vancouver Coastal Health authority region from 2011 to 2016 that were assessed for MMR deficiency. Primary outcome measures were recurrence rates expressed per person-years (py), progression free survival (PFS) and overall survival (OS) calculated using Kaplan-Meier method and log-rank tests. Cox proportional hazards model estimated the association between MMRd and recurrence/death after adjustment for covariates. Results: There were 477 low-risk patients, including 132 MMRd (27.7%) and 345 MMRp (proficient) patients. Women with MMRd tumors had higher recurrence rates (3.53p100py vs 1.21p100py) and worse PFS (p=0.0086) compared to women with MMRp tumors. After adjustment for age, LVSI status, adjuvant therapy, and post-operative grade, MMRd status remained associated with a higher risk of recurrence (HR 2.99, 95% CI 1.27–7.04). There was no significant difference in OS between MMR groups (HR 1.38, 95% CI 0.57–3.33). Conclusion: In low-risk stage IA grade 1 or 2 endometrioid endometrial cancers, MMR deficiency is associated with a higher recurrence rate than in MMR proficient cases, after adjustment for covariates, implying that MMR deficiency reflects a different biology in endometrial cancer. Disclosure: Nothing to disclose.